THE IMPACT OF CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION: A BIBLIOMETRIC APPROACH - Prabowo Tejo Susetyo; Siti Dyah Handayani; Retno Widowati (International Journal Management and Economic, 2024)
Consumer experience refers to a series of events that consumers go through while shopping or conducting transactions. A positive consumer experience can lead to customer satisfaction, while a negative experience can result in dissatisfaction. This study aims to examine the impact of customer experience on customer satisfaction. The research method employs a bibliometric approach, involving nationally and internationally reputable articles published on Google Schooler. The conclusion from the research results analysis shows that citation analysis is a valuable tool for evaluating the influence of academic works, particularly in the context of customer experience. The data indicates that 2020 was a peak year for productivity, with two key studies receiving significant attention from the academic community, emphasizing their relevance in the fields of customer experience and satisfaction. This research also highlights that the theme of customer experience has rapidly developed across various domains, including tourism and hospitality management, with numerous publications in leading journals. Furthermore, the trend analysis reveals a strong connection between customer experience and factors such as satisfaction and loyalty, as well as a growing interest in technological aspects that influence customer interactions. Therefore, there are ample opportunities for further exploration of key themes and emerging trends in customer experience research.